Application of Edible Film from Mung Bean Starch with the Addition of Glycerol Plasticizer on Broccoli - Setiani, Ugi Asih; Sedyadi, Endaruji; Rahmayanti, Maya; Warsito, Gita Miranda (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2025)
The research on making edible film from mung bean starch with glycerol plasticizer as broccoli packaging aims to determine the characteristics of the edible film from mung bean starch with glycerol addition and its effect on broccoli weight loss. This study involved three stages, which include producing mung bean starch, making and characterizing the edible film, and applying the edible film on broccoli. The glycerol concentrations added were 25.2%, 31.5%, and 37.8% of the starch weight used. The edible film characteristics tested were thickness, tensile strength, elongation, Young's modulus, water vapor transmission rate (WVTR), and ash content. The application test on broccoli lasted 9 days. Results showed that thickness, tensile strength, and ash content met edible film standards, while elongation, Young's modulus, and WVTR did not meet applicable standards. Broccoli coated with the edible film had lower weight loss compared to the control.